Does marginal employment promote regular employment for unemployed welfare benefit recipients in Germany? - Torsten Lietzmann; Paul Schmelzer; Jürgen Wiemers (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
Marginal employment (ME) is one of the largest forms of atypical employment in Germany. In this study, we analyse whether ME has a "stepping stone" function for unemployed individuals, i.e., whether ME increases the subsequent probability of regular employment. Our study adds to the literature in the following ways. First, compared to previous studies, it analyses the "stepping stone" function for a more recent time period, i.e., after Germany's major labour-market reforms (Hartz reforms) at the beginning of the 2000s. Second, we use a new administrative data source which includes previously unavailable information on desired labour supply and household composition. Third, we follow recent methodological developments in the evaluation literature by applying a dynamic evaluation approach that has not previously been used to analyse marginal employment. Our results for single and childless unemployment benefit-II recipients highlight the importance of the dynamic approach: We find differing treatment effects by unemployment duration. According to our results, marginal employment does increase the likelihood of regular employment within a three-year observation period only for those unemployed who take up ME several months after beginning to receive benefits. In contrast, for those starting ME within the first months of receiving benefits, there is no effect on the probability of regular employment. – – In dieser Studie untersuchen wir, ob geringfügige Beschäftigung eine "Brückenfunktion" für arbeitslose ALG-II-Bezieher hat, d. h., ob geringfügige Beschäftigung für diese Gruppe nachfolgend die Wahrscheinlichkeit einer regulären Beschäftigung erhöht. Unsere Studie erweitert die bestehende Literatur in mehrfacher Hinsicht. Erstens betrachten wir im Vergleich zu früheren Untersuchungen erstmalig die Brückenfunktion geringfügiger Beschäftigung nach Einführung der Hartz-Reformen. Zweitens verwenden wir einen neuen administrativen Datensatz, der bisher nicht verfügbare Informationen zum gewünschten Erwerbsumfang und zur Haushaltszusammensetzung enthält. Drittens verwenden wir einen dynamischen Matching- Ansatz, der hier erstmalig zur Analyse der Brückenfunktion geringfügiger Beschäftigung eingesetzt wird. Dieser Ansatz erlaubt es, die Brückenfunktion in Abhängigkeit vom Zeitpunkt der Aufnahme der geringfügigen Beschäftigung zu untersuchen. Unsere Ergebnisse zeigen, dass geringfügige Beschäftigung die Wahrscheinlichkeit regulärer Beschäftigung innerhalb einer dreijährigen Beobachtungsperiode nur für solche arbeitslosen Leistungsbezieher erhöht, die die geringfügige Beschäftigung erst mehrere Monate nach Eintritt in den ALG-II-Bezug aufgenommen haben. Im Gegensatz dazu finden wir keine Brückenfunktion für Personen, die die geringfügige Beschäftigung innerhalb der ersten Monate des Leistungsbezugs aufgenommen haben.
Keywords: J64; J20; J08; C14; 330; Evaluation; Atypical employment; Administrative data; Propensity score matching; Hidden bias